Comment: pregnancy after bariatric surgery – achievements and open questions - Christian S. Göbl; Michael Feichtinger; Wolfgang Henrich (BMC Pregnancy and Childbirth, 2023)
Abstract Bariatric surgery confers potential advantages for obese patients, but also risks for pregnancy. Perinatal outcomes may be varying between surgical procedures. This topic was recently addressed by a systematic review in BMC Pregnancy and Childbirth. This commentary will discuss the scientific background and implications for future research.